Ultraviolet light in water and wastewater sanitation - Masschelein, Willy J., ....-; Rice, Rip G., ....- (Boca Raton : Lewis, 2002)
1.Introduction 2.Available lamp (or burner) technologies 3.Use of ultraviolet light for disinfection of drinking water 4.Use of ultraviolet in photochemical synergistic oxidation processes inwater sanitation 5.Use of ultraviolet light for sanitation of wastewater 6.General conclusions
Keywords: Afvalwaterzuivering; Desinfectie; Drinkwaterzuivering; Ultraviolet licht